Lead contamination in coastal sediments, Buyat Bay: Spatial assessment in North Sulawesi, Indonesia - Rondonuwu, Glorya; Maddusa, Sri Seprianto; Umboh, Jootje (SAMATA JOURNAL OF PUBLIC HEALTH SCIENCE, 2026)
Heavy metal contamination remains a persistent environmental and public health concern in coastal ecosystems, yet recent information on lead (Pb) accumulation in Buyat Bay sediments is limited; this study provides an updated site-specific assessment of Pb distribution and sediment-quality status. This study aimed to analyze Pb concentrations in sediments of Buyat Bay, North Sulawesi, Indonesia, and compare the measured values with the National Oceanic and Atmospheric Administration (NOAA) Sediment Quality Guidelines. A descriptive survey design was applied through field sampling and laboratory analysis. Sediment samples were collected from 16 purposively selected sampling points in November 2025 and analyzed at the Center for Health Laboratory of Makassar using Inductively Coupled Plasma–Mass Spectrometry (ICP-MS). Pb was detected in all sediment samples, with concentrations ranging from 2.6145 to 30.2823 µg/g and an average concentration of 6.7405 µg/g. The highest concentration was recorded at Point 9, indicating spatial variation in Pb accumulation across the bay. All concentrations were below the NOAA Effects Range Low value of 46.7 µg/g, suggesting a relatively low probability of adverse biological effects. Nevertheless, the widespread detection of Pb supports continued environmental surveillance, integrated monitoring of sediments and marine biota, and preventive coastal management to minimize future ecological and public health risks.